Role of microglia autophagy and mitophagy in age-related neurodegenerative diseases - Lin, Mingkai; Yu, Hongwen; Xie, Qiuyan; Xu, Zhiyun; Shang, Pei (Frontiers in Aging Neuroscience, 2023)
Microglia, characterized by responding to damage, regulating the secretion of soluble inflammatory mediators, and engulfing specific segments in the central nervous system (CNS), function as key immune cells in the CNS. Emerging evidence suggests that microglia coordinate the inflammatory responses in CNS system and play a pivotal role in the pathogenesis of age-related neurodegenerative diseases (NDDs). Remarkably, microglia autophagy participates in the regulation of subcellular substances, which includes the degradation of misfolded proteins and other harmful constituents produced by neurons. Therefore, microglia autophagy regulates neuronal homeostasis maintenance and process of neuroinflammation. In this review, we aimed at highlighting the pivotal role of microglia autophagy in the pathogenesis of age-related NDDs. Besides the mechanistic process and the co-interaction between microglia autophagy and different kinds of NDDs, we also emphasized potential therapeutic agents and approaches that could be utilized at the onset and progression of these diseases through modulating microglia autophagy, including promising nanomedicines. Our review provides a valuable reference for subsequent studies focusing on treatments of neurodegenerative disorders. The exploration of microglia autophagy and the development of nanomedicines greatly enhances current understanding of NDDs.